Analysis of automotive paint fragments used as forensic evidence by Raman spectroscopy - Gutiérrez-Fallas, Dionisio (2016)
Frequently, in many traffic accidents it is difficult to establish responsibilities for material damages, people injuries or death, because people that have been involved in the accident leave the crime scene. Because of that, it is very important to find automotive evidence, like paint fragments, as forensic proof that could help authorities reconstruct the incident. The study of physical characteristics of the fragments could help simplify the identification of the vehicle they come from. Commonly, the fragments are very small, in millimeter order size; therefore, it is essential to examine e the samples without risk of destruction, usually by microscopic and spectroscopic techniques. In this work, optical microscopic and Raman spectroscopy analysis of some automotive paint fragments are shown, especially to introduce the Raman spectroscopy as a complementary analytical technique to obtain forensic evidence.